Analysis of The Influence of Organizational Culture and School Principal Leadership Style on Performance of Private National High School Teachers - Yoga Fortuna Wisnu Wardana; Sudirman Sudirman; Reza Saeful Rachman; Arman Paramansyah; Akhmad Ramli (Journal on Education, 2024)
This study assesses how principal leadership style and school culture affect teacher effectiveness. Through observations, interviews, and questionnaires, data were gathered from the 100 teachers who completed the quantitative survey. The data were tested using a correlation method, simple and multivariate regression analysis, and other techniques. With an R2 (Coefficient of Determination) of 25%, the findings demonstrated that the principal's leadership style had a favorable and substantial influence on teacher performance. The teacher performance score increased to 72.5 with a one-unit rise in the principal's leadership style score, according to simple linear regression. With an R2 of 27%, school culture also significantly and favorably affects teacher performance. According to the regression, a teacher's performance score of 70.8 will rise with every unit that the school culture score rises. There will be a 48.4 improvement in teacher performance for every point that the principal leadership style and school culture scores are raised, either alone or together